Case studies in operational culture - Holmes-Eber, Pamela; Mainz, Marcus J (Marine Corps University Press, 2014)
This book provides an important record of the cultural lessons learned during the past decade not only in Afghanistan and Iraq but in a variety of operations around the globe. Case Studies in Operational Culture draws together the experiences of 22 field grade military officers from the U.S. Army, Navy, Air Force and Marine Corps, as well the Canadian and Australian military. Applying the cultural concepts described in two previous books in this series Operational Culture for the Warfighter and Applications in Operational Culture these cases provide detailed, concrete illustrations of how specific cultural factors had a direct impact on the outcome of military operations. As these case studies illustrate, cultural considerations are not merely a tactical concern focused on building good relations with local communities; indeed, they are critical if the United States and its allies hope to create effective plans and strategic solutions that depend upon the cooperation of culturally diverse partners in a region.